ASSESSING THE ABILITY OF PREOPERATIVE QUANTITATIVE SPECTRAL-DOMAIN OPTICAL COHERENCE TOMOGRAPHY CHARACTERISTICS TO PREDICT VISUAL OUTCOME IN IDIOPATHIC MACULAR HOLE SURGERY. Issue 1 (January 2021) - Mehta, Nitish; Lavinsky, Fabio; Larochelle, Ryan; Rebhun, Carl; Mehta, Nihaal B.; Yanovsky, Rebecca L.; Cohen, Michael N.; Lee, Gregory D.; Dedania, Vaidehi; Ishikawa, Hiroshi; Wollstein, Gadi; Schuman, Joel S.; et al.
Abstract : Purpose: To determine which spectral domain optical coherence tomography biomarkers of idiopathic macular hole (MH) correlate with the postoperative best-corrected visual acuity (BCVA) in anatomically closed MH. Methods: Retrospective analysis of spectral domain optical coherence tomography scans of 44 patients presenting with MH followed for a mean of 17 months. Widths of MH aperture, base, and ellipsoid zone disruption were calculated from presenting foveal spectral domain optical coherence tomography B-scans. Macular hole base area and ellipsoid zone disruption area were calculated through the custom in-house software. Results: Poorer postoperative BCVA correlated with increased preoperative choroidal hypertransmission (r = 0.503, P = 0.0005), minimum diameter (r = 0.491, P = 0.0007), and base diameter (r = 0.319, P = 0.0348), but not with preoperative ellipsoid zone width (r = 0.199, P = 0.2001). Applying en-face analysis, the BCVA correlated weakly with preoperative ellipsoid zone loss area (r = 0.380, P = 0.013), but not with preoperative MH base area (r = 0.253, P = 0.1058). Conclusion: Increased MH minimum diameter, base diameter, base area, and choroidal hypertransmission are correlated with a poorer postoperative BCVA. Ellipsoid zone loss measurements were not consistently correlated with a BCVA. Choroidal hypertransmission width may be an easy-to-visualize predictive imaging biomarker in MH surgery. Abstract : Comparison of preoperative spectral domain optical coherence tomography biomarkers to the last postoperative visual acuity in eyes with idiopathic macular hole revealed a correlation with minimum diameter, base diameter, base area, and choroidal hypertransmission and no relationship with ellipsoid zone loss measured from both B-scan and en-face imaging.